2012
DOI: 10.1111/cbdd.12047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐HIV Properties of New Carbamate Prodrugs of AZT

Abstract: A series of new 5¢-O-carbamate prodrugs of AZT have been prepared. The stability in biological media, anti-HIV properties and pharmacokinetic parameters in dogs were evaluated. The compounds display moderate anti-HIV activity in cell culture. After oral administration of carbamate IV in dogs, both intact prodrug IV and released AZT were discovered in dog blood. Pharmacokinetic parameters of the compound IV were estimated. Half-life (T 1 ⁄ 2 ) of AZT released after oral administration of IV in dogs was close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…8,10,12,14,17 As stated before, the chemical stability of the resulting prodrugs represents a critical issue for their pharmacotherapeutic performance since its extent constitutes a key event in the reconversion to the bioactive NRTIs. Previous results obtained at our and other laboratories demonstrated that AZT carbamates are highly resistant to chemical and enzymatic hydrolysis, 18,19 while carbonate and ester based prodrugs exhibit a wide stability range depending on their chemical nature. 20,21 Also, a careful selection of the molecular complement for the design of a double prodrug is required from the beginning because the stability of the chemical bond between the NRTIs and the linker chain may be affected by the added chemical moiety, as demonstrated for a series of AZT prodrugs obtained by our research group by combining AZT oxalic acid ester and several aminoacids.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…8,10,12,14,17 As stated before, the chemical stability of the resulting prodrugs represents a critical issue for their pharmacotherapeutic performance since its extent constitutes a key event in the reconversion to the bioactive NRTIs. Previous results obtained at our and other laboratories demonstrated that AZT carbamates are highly resistant to chemical and enzymatic hydrolysis, 18,19 while carbonate and ester based prodrugs exhibit a wide stability range depending on their chemical nature. 20,21 Also, a careful selection of the molecular complement for the design of a double prodrug is required from the beginning because the stability of the chemical bond between the NRTIs and the linker chain may be affected by the added chemical moiety, as demonstrated for a series of AZT prodrugs obtained by our research group by combining AZT oxalic acid ester and several aminoacids.…”
Section: Introductionmentioning
confidence: 78%
“…In particular, the design of prodrugs of NRTIs constitutes a very promising strategy, and has been widely applied to the preparation of prodrugs of AZT that may exhibit enhanced pharmacotherapeutic properties. [8][9][10][11][12][13] Considering that NRTIs require phosphorylation of the 5 0 -OH to exhibit anti-HIV activity, 1 many prodrugs have been prepared by derivatization of this position to design inactive compounds that require chemical and/or enzymatic hydrolysis before bioactivity is regained. With this strategy in mind, the possibility of rationalizing and/or predicting the extent of chemical and/or enzymatic reconversion is a keystone for the design of new prodrugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 2 ( Figure 2) was most potent (EC50 = 3.2 μM) derivative having a free amino group attached with the carbonyl group. All derivative were chemically stable (T1/2 > 24) and compound 3 generated the active drug slowly (T1/2 = 8 hr) as compared to the other derivatives [20]. The problem of oral bioavailability and toxicity of AZT can be minimized by using the dipeptide ester prodrugs of AZT.…”
Section: Modifications At 5'-hydroxyl Groupmentioning
confidence: 99%
“…Significant efforts have been made to overcome AZT suboptimal pharmacokinetic properties by applying different chemical strategies. In particular, the design of prodrugs constitutes a very useful approach towards the possibility of improving most of the pharmacokinetic properties of AZT; [12][13][14][15][16] it is especially focused on the possibility of increasing its bound fraction to HSA and to modulate its cytotoxicity. AZT requires several phosphorylation steps on it 5´OH position in order to gain bioactivity, process that is selectively catalized by cytosolic thymidine kinase enzymes.…”
Section: Figurementioning
confidence: 99%